Talking Across the Table: A Dialogue on Women, Welfare, and Adult Education - Elisabeth Hayes; Barbara Sparks; Catherine Hansman; Mechthild Hart; Vanessa Sheared (Adult Education Research Conference, 1998)
Introduction: Welfare reform is a current societal issue of tremendous significance in the United States. The popular discourses surrounding welfare reform are extremely complex and lead to frequently volatile discussions, for welfare reform itself is not a single issue, but relates to multiple underlying issues concerning the origins and solutions of poverty and unemployment, the subordination of women and women=s roles in society, competing discourses of work and family, the intersections of racism and poverty, and the role of adult education in social change. Welfare reform as a societal issue affects us all as citizens and participants in the U.S. economic and political system. But more specifically, as adult educators, we have a potentially vital role to play as these issues are debated and translated into policy and practice. New policies are having a tremendous impact on the nature of adult education programs for the economically disenfranchised. Further, welfare reform has stimulated nonformal learning and popular education in connection with the work of social action groups, such as the Welfare Warriors, organizing in reaction to reform initiatives. Perhaps most importantly, welfare reform puts forward in a compelling manner the question of adult educators= responsibility to take a proactive role in social change efforts (Cunningham, 1989).